Islamic Economic Perspective and Potential of Zakah Imposement on Cryptocurrency - Rozi Irfan Rosyadhi; Abu Salim (Journal of Islamic Economic Laws, 2022)
Indonesia is the home country for many Muslim, management and effectiveness of zakah is essential to the society. In the era of digital technology government imperative to use technology to improve the classical zakat administration ensure the transpiration and principle of easiness payment of zakah. This paper giving study of perspective of the economic islam and potential application zakah on cryptocurrency. This  is a qualitative approach where the primary resource from Indonesia zakah administration laws and the secondary source as journal, article and published report. The finding of this paper suggest that government and NGO should give facility and accepting payment zakah in crypto, the capability of transfer is more transparent and cross the border of the country using blockchains technology. Give society more secure and trust in zakah organization in Indonesia. This research will assist the zakah administration in Indonesai to adopt technology in this regard.